10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Despite the emergence of various "health coaches" in recent decades, little is known about the nature of their work in addressing medicalized conditions. Utilizing in-depth interviews with 51 ADHD coaches, participant observation data from 7 ADHD national symposia, and qualitative content from ADHD coach publications, I examine access to and characteristics of the practice of coaching for a classic case of medicalization: attention deficit hyperactivity disorder (ADHD). Findings indicate certain elements of a neoliberal and consumerist response to what is perceived to be limited, prescriptive, hierarchical medical care. Often drawing upon personal experiences and working with "clients" as opposed to "patients," ADHD coaches characterize their practice as highly-tailored support grounded in partnership, accountability, accessibility, and choice - factors often facilitated by the use of digital technologies. Client empowerment is partially constrained and coach/provider empowerment is partially enhanced, however, by determinations of "coachability," an emphasis on individual responsibility, and limited reimbursement options. Additionally, findings point to the role that intersecting stakeholder identities (e.g., clinician/coaches, coach/clients) may play in such dynamics. I discuss the relevance of such findings for theorizing about the engaged health client within an era of increased health consumerism, corporatization, growing and intersecting forms of "expertise," and increased personal responsibility over health.